KONSERVASI EKOSISTEM MANGROVE DI DESA DOMPAS KABUPATEN BENGKALIS - Thamrin Thamrin; Rahmadi Rahmadi (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2023)
The mangrove ecosystem in Dompas Village, Bengkalis Regency, has been degraded due to anthropogenic activities and pollution from both land and sea. This study aims to analyze the condition of the mangrove ecosystem and the urgency of conservation in the coastal area of Dompas Village. The methods used were field surveys, observation of the mangrove ecosystem, measurement of physical and chemical parameters of the water, and interviews with the local community. The results of the study show that the mangrove ecosystem in Dompas Village has experienced a decline in quality due to uncontrolled logging, pollution from the Pertamina Sungai Pakning oil refinery, and shipping activities. Mangrove degradation has caused coastal abrasion, a decline in biodiversity, and a reduction in fishery resources. Conservation of the mangrove ecosystem is crucial to maintain ecological functions, protect the coastline, preserve biodiversity, and support the livelihoods of coastal communities. Rehabilitation efforts, community education, enforcement of regulations, and integrated coastal zone management are needed to ensure the sustainability of the mangrove ecosystem in Dompas Village.